Inhibition of Notch 1 receptor influenced the differentiation of Lin-CD45RA-dendritic cell precursors within ovarian carcinoma microenvironment. (December 2016) - Qian, Xue-qian; Chen, Li-li; Cheng, Qi; Tian, Yang; Luo, Xiao-feng; Wan, Xiao-yun
Abstract Background Previous evidence suggested that the differentiation of Lin-CD45RA-DC precursors were prior to plasmcytoid dendritic cells (pDCs) than myeloid dendritic cells (mDCs) within ovarian cancer microenvironment. However, the mechanism is still unclear. Therefore, we investigated the function of Notch 1 signal pathway in the differentiation of Lin-CD45RA-DC precursors. Methods The CD34+ hematopoietic stem cells were extracted from umbilical cord blood in term parturition, and Lin-CD45RA-DC precusors were separated and induced mature. Expression of Notch1 receptor and ligands in Lin-CD45RA-DC precusors was detected by Real-time PCR and was down-regulated by shRNA or γ-secretase inhibitor (GSI). Flow cytometry was used to analyze the subset of DCs with or without SKOV3 culture supernatants. IL-12 level was detected by ELISA. Results Expression of Notch1 receptors and ligands were detected in Lin-CD45RA-DC precursor cells. The Notch1 mRNA in Lin-CD45RA-DC precursors can be down-regulated by shRNA-Notch1 lentivirus transfection and GSI. ShRNA mediated Notch 1 knock-down significantly differentiated less plasmcytoid dendritic cells (pDCs), but generated more myeloid dendritic cells (mDCs), and this would not be influenced by the supernatant of the ovarian carcinoma cell line. GSI had the same effect in the differentiation of pDC. The secretion of IL-12 significantly increased after Notch1 knock-down with or without SKOV3 culture supernatants. Conclusions Notch1 is an important signaling pathway in the differentiation of Lin-CD45RA-DC precursor cells to plasmcytoid dendritic cells (pDCs). And this would not be affected by the supernatant of the ovarian carcinoma cell line.